Intelligent Computing Research Studies in Life Science: Life Sciences-Health Care - Dr.S.Thilagamani, Guest Editor (International Journal of Life Science and Pharma Research, 2019)
This special issue is highly related to communication and software application for medical and health care systems towards providing safe, enhanced service to the society. Also it focuses on integration of artificial intelligence to the man kind. In addition, Environmental issues, agricultural advancements, security issues, medical therapies and many more related to artificial intelligences (AI) are been focused in this issues. Artificial intelligence for Cloud computing in health care, for diagnosis in health care, for safety in day to day life, for biorhythm monitoring for the man kind health needs are the need of the hour for the society needs. This special issue focuses on those aspects with much implication for the health care. The articles published in this special issue will certainly bring as positive effect for the developing health care and to make use of available resources and to remove certain obsolete factors and process which may delay or harm the existing health care system. It enhances maximum utilization of scientific knowledge to potentiate therapy and diagnosis in the health care system.